808 nm light responsive nanotheranostic agents based on near-infrared dye functionalized manganese ferrite for magnetic-targeted and imaging-guided photodynamic/photothermal therapy. Issue 9 (16th February 2017) - Deng, Kerong; Chen, Yinyin; Li, Chunxia; Deng, Xiaoran; Hou, Zhiyao; Cheng, Ziyong; Han, Yanqiu; Xing, Bengang; Lin, Jun
Abstract : Schematic diagram of 808 nm light mediated antitumor nanotheranostic agents for synchronous magnetic targeted and MR imaging guided photothermal/photodynamic therapy. Abstract : Near-infrared (NIR) light induced phototherapy has attracted considerable attention due to its deep therapeutic depth. To improve the therapeutic outcome and address non-selective side effects, the combination of complementary phototherapeutic strategies in a single nanoagent with precise targeting ability may provide an effective approach for cancer therapy. Thus we have developed an 808 nm NIR light triggered nanosystem based on IR806 dye functionalized MnFe2 O4 (MFO-IR) for synchronous magnetic targeted and magnetic resonance (MR) imaging guided in vivo photodynamic/photothermal synergistic therapy. In this construction strategy, carboxylic acid functionalized NIR dye IR806 is explored as an 808 nm NIR-excited photosensitizer (PS) for the first time, which can also provide a conjugation site for MnFe2 O4 nanoparticles (MFO NPs). Here, monodisperse MFO NPs have multiple capacities as dye carriers, targeting ligands, MRI contrast agents and photothermal agents. MFO-IR nanocomposites (NCs) with negligible toxicity present efficient NIR-mediated photothermal damage and ROS cytotoxicity via the relevant in vitro experimental investigations. With ideal magnetic targeting effects and remarkable NIR light-responsive properties, these MFO-IR NCs exhibit high in vivo tumor localization and could destroy subcutaneous solid tumors completely under an external magnetic field and 808 nm laser irradiation. Consequently, this magnetic nanosystem has great potential for simultaneous diagnosis and precise cancer phototherapy.